Development of Teaching Material Vocabulary with the Mnemonic Keyword - Khairunnisah, Khairunnisah; Hasibuan, Apriyanti; Purba, Happy Sri Rezeki (Journal of English Teaching and Learning Issues, 2018)
This research aimed at developing an integrated and creative English learning materials for grade IX students of SMP. The operational purpose are: (1) determining the design of learning material, (2) describing the result of validation by the expert of content, media and instructional design, (3) describing the result of validation by colleague and students, and (3) describing the result of the implementation try out. The subjects of evaluation were, 2 instructional experts, 2 colleagues, 10 students, and 30 students for the implementation try out. The data was collected using quetionair and test. The result of evaluation was analyzed through quantitative and qualitative descriptive technique. The results showd: (1) validation over draft I by the exspert of content 84,14%, and design 88,88%, the qualification is almost perfect, light revision was done (2) validation over draft II by colleagues 89,63% and by students from small class was 74% and big class was 75,33%, the qualification was good, light revision was done, and the students’worksheet, and the result showed that the students’ ability in vocabulary mastery more increase. This research gave outcomes for English education field, that is book for study vocabulary and for vocabulary enrichment in first level.